Kontribusi Perempuan dalam Bernegara (Studi Budaya dan Komunikasi Politik di Kalimantan Selatan): Women's Contribution to the State (Cultural Studies and Political Communication in South Kalimantan) - Ikhsan, Favi Aditya; Husni, Muhammad; Noor, Muhammad (Anterior Jurnal, 2025)
In the current political stage phenomenon, not only men but also women are actively involved in politics in contributing to the state. The purpose of the study is to reveal the extent of the contribution of political women in the world of parliament or the executive from the perspective of political communication and culture that is developing in South Kalimantan society. This study uses a qualitative research method in the form of collecting field data, namely observation, in-depth interviews, and documentation. The library data is taken from research article data through the same research journal in the form of other writings, namely reference books, monographs, books, media coverage, and textbooks as sources. The study found that the contribution of political women in the state of South Kalimantan in terms of political communication and culture is to give birth to political work and involvement in the cultural approach of the community to be able to approach constituents during the campaign-elected to produce policies. In voicing aspirations in the parliamentary chamber for 4 female legislators in this study, including being able to implement programs during the campaign. Along with that, the mission of the Regent of Barito Kuala as the first regional head executor in South Kalimantan when leading Barito Kuala Regency was able to answer his mission well. Thus, political women entering the world of politics is proof of the political work that has been done by these 5 female politicians in front of the public.